2018
DOI: 10.12659/msm.906489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Intervention on Serum Levels of Fibroblast Growth Factor 23 (FGF23) in Chinese Adults: An Intervention Study

Abstract: BackgroundFibroblast growth factor 23 (FGF23), a prominent regulator of phosphate and calcium metabolism, regulates sodium excretion in distal tubules through sodium-chloride cotransporter. This effect regulates blood pressure. Salt intake exerts effects on serum levels of FGF23 in mice. The aim of this study was to explore whether salt intervention affects serum concentrations of FGF23 in Chinese adults.Material/MethodsWe enrolled 44 participants from Lantian, a rural community of Shaanxi, China. All particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…↓1, 25 the expected increase in BP and resulted in a significant decline of FGF23 levels [106], thus supporting the notion that changes in Na intake induce opposing regulatory changes in FGF23.…”
Section: Nonpharmacologic Interventionssupporting
confidence: 60%
“…↓1, 25 the expected increase in BP and resulted in a significant decline of FGF23 levels [106], thus supporting the notion that changes in Na intake induce opposing regulatory changes in FGF23.…”
Section: Nonpharmacologic Interventionssupporting
confidence: 60%
“…A recent study demonstrated an inverse correlation between 24‐hour urinary sodium levels and serum FGF23 concentrations in healthy adults. 27 As all participants of this study were prescribed a special diet restricting salt consumption during the treatment, we felt it was unlikely that salt intake played a confounding role in the antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As described before, this intervention study included three periods, namely, a 3-day normal diet, a 7-day low-Na + diet (51.3 mmol/d sodium or 3.0 g/d NaCl), and a 7-day high-Na + diet (307.7 mmol/d sodium or 18 g/d NaCl) ( Figure 2). 11…”
Section: Dietary Interventionmentioning
confidence: 99%
“…Previously, we, as well as other researchers, found salt intake could influence serum level of FGF23. 11,21,22 As one of the key As mentioned above, the dysregulation of sodium excretion played pivotal role in the development of salt sensitivity. We found the regulation of serum FGF23 by salt intake was more prominent in salt-resistant participants in previous study.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation